Pencegahan Seks Bebas Dengan Konseling Guru PAK dan Edukasi Seks di SMA Swasta Nabire - Kamalia, Cici; Hendro, Nikotitoli Thomas (Jurnal Teologi dan Pendidikan Kristen, 2023)
This study aims to determine how much the contribution of counseling guidance (X1) and sex education (X2) to free sex prevention (Y). The research was conducted on Nabire TP 2022-2023 private high school students. The population was all 120 students and 60 people were sampled. Research institutions used questionnaires to capture data on three variables. The results of the study concluded that there was a contribution from counseling guidance (X1) to sex prevention (Y) at the zero level Ry.1=40.19%, for the Counseling Guidance variable (X1) there was a contribution from sex education (X2) to sex prevention (Y) at the zero level Ry.2=34.105%, while counseling guidance (X1) 20 students tended to be quite good (33.34%), education about sex (X2) 21 students tended to be quite good (35%) and sex prevention in students (Y) 28 students tended to be quite good (46, 66%). The results of this study concluded that the minimal/low contribution of CE teacher counseling guidance on sex prevention, it is recommended that CE teachers in state high schools in Nabire provide more excellent knowledge and understanding of students about sex and how to prevent free sex. CE teachers must be sensitive and concerned about all problems faced by students including in terms of student association both with peers and other adults outside and inside the school environment for the prevention of free sex because it greatly contributes to students' understanding of sex